초심 수퍼바이저의 역전이 경험과 의미연구 - 김명화(Myong-Hwa Kim); 홍혜영(Hye-Young Hong) (한국콘텐츠학회 논문지, 18(9), 2018)
The objective of this study was to understand the countertransference and its meanings, experienced by novice supervisors in the supervision. For this, total seven novice supervisors with supervision experience for five years or less were purposively sampled, and then the in-depth interviews were conducted. As a phenomenological research, the collected data was analyzed in accordance with the Giorgi's 4-Stages, suitable for discovering the phenomenon and its meanings, experienced by research participants. In the results, there were six themes such as 'difficulty to realize the countertransference', 'expectation and impatience of supervisee's growth', 'identification with supervisee', 'hope for maintaining a good relationship with supervisee', 'avoidance of supervision', and 'struggle for standing up as an expert'. The unsolved problems and desires of novice supervisors were revealed as countertransference, which influenced the supervision. The results of this study imply that the countertransference of supervision has not only negative aspects, but also a positive meaning in the aspect that they could deeply understand themselves and others. 본 연구의 목적은 초심 수퍼바이저가 수퍼비전에서 경험하는 역전이와 그 의미를 알아보기 위하여 시행되었다. 이를 위하여 수퍼비전 경력 5년 이하인 초심 수퍼바이저 7명을 연구 참여자로 의도 표집 하여 심층면접을 실시하였다. 수집된 자료는 현상학적 연구로 참여자가 경험한 현상과 의미를 발견하는데 적합한 Giorgi의 4단계 따라 자료를 분석 하였다. 그 결과 '역전이 자각의 어려움', '수퍼바이지의 성장에 대한 기대와 조급함', '수퍼바이지와 동일시', '수퍼바이지와 좋은 관계 유지에 대한 바람', '수퍼비전에 대한 회피', '전문가로 서기 위한 고군분투'의 6가지 주제로 나타났다. 초심 수퍼바이저들의 미해결된 문제와 욕구가 역전이로 나타나고 있었고 이로 인하여 수퍼비전에 영향을 주고 있었다는 것을 깨닫게 되었다. 수퍼비전에서의 역전이는 부정적인 면만 존재하는 것이 아니라 자신과 타인을 깊이 이해하게 된다는 점에서 긍정적인 의미를 가지고 있음을 시사한다.